Revealed Comparative Advantage and Competitiveness in Hungarian Agri-Food Sectors Technology Foresight in Hungary - Imre Ferto; Lionel J. Hubbard (Hungarian Academy of Sciences, Institute of Economics, 2002)
This paper investigates the competitiveness of Hungarian agriculture in relation to that of the EU employing four indices of revealed comparative advantage, for the period 1992 to 1998. Consistency tests implies that the indices are less satisfactory as cardinal measures, but are useful in identifying whether or not Hungary has a comparative advantage in a particular product group. The results suggest that despite of significant changes in Hungarian agriculture during the 1990s, the pattern of revealed comparative advantage has remained fairly stable. RCA indices, despite their limitations, provide a useful guide to underlying comparative advantage and offer a further insight into the competitiveness of Hungarian agri-food sectors and the implications for trade when membership of the EU becomes a reality.
Keywords: 330